Peran Jaringan Sosial dalam Proses Pencarian Kerja Mahasiswa (Studi Kasus Mahasiswa UMSU Jurusan Manajemen Bisnis Syariah) - Sinaga, Risva Nanda; Novien Rialdy (Lembaga Intelektual Muda Maluku, 2024)
This study aims to investigate the role of social networks in the job search process among students of Universitas Muhammadiyah Sumatera Utara (UMSU), particularly in the Islamic Business Management program. In the context of globalization and increasing competition in the job market, the utilization of social networks has become an important strategy for students to enhance their chances of securing employment. This research employs a qualitative method by collecting data through in-depth interviews with 15 purposively selected students. The findings indicate that social networks, which include relationships with friends, alumni, and the use of social media, have a significant impact in assisting students in obtaining information about job vacancies and receiving recommendations. These results highlight the importance for students to actively leverage their social networks to improve their job prospects after graduation. It is hoped that the findings of this study can provide deeper insights and a better understanding for students, universities, and relevant stakeholders regarding the significance of social networks in supporting the transition from education to the workforce